Multiple Injections of Cryopreserved Fetal Liver Cells to Ageing Rats Prevent Age-Related Antioxidant System Changes and Increase Lifespan - Ochenashko, Olga V.; Nikitchenko, Yuriy V.; Petrenko, Oleksandr Yu. (Problems of Cryobiology and Cryomedicine, 2019)
In the present work, the possibility of using cryopreserved fetal liver cells (ÑFLC) as an anti-aging agent, assessing their effect on the prooxidant-antioxidant balance, the physiological parameters and the life span of aging rats was investigated. It has been established that the repeated administration of ÑFLC (every 3 months) to adult rats from 13 to 22 months of age, prevents changes in the prooxidant-antioxidant balance of the liver and blood that form in older animals by 25 months. Similar multiple injections of ÑFLC to old rats (from 23 months to the end of life) contribute to weight gain, hamper the reduction in the quality of the coat and prolong the life span of experimental rats by 100 days. The results of the work allow considering the transplantation of ÑFLC as a promising approach for correcting the age-related changes associated with the development of oxidative stress. Â  Probl Cryobiol Cryomed 2019; 29(3):Â 221â€“236.